HUBUNGAN ANTARA PEKERJAAN MANUAL HANDLING DENGAN KELUHAN MUSCULOSKELETAL DISORDERS PADA PENAMBANG BATU ANDESIT - Wahyudin Wahyudin; Idham Latif; Nadia Zulfa Amelia; Setyo Dwi Widyastuti (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Village X is one of the largest andesite mining areas in Majalengka Regency, with a high risk of workplace accidents due to traditional mining practices that still rely on manual handling. The use of human labor in a manual manner can lead to complaints of musculoskeletal disorders (MSDs). Based on a preliminary study conducted on April 13, 2024, it was found that 5 out of 6 stone miners experienced high-level complaints of musculoskeletal disorders. This research aims to determine the relationship between manual handling work and complaints of musculoskeletal disorders. The research method used is quantitative with a cross-sectional approach. The sample in this study consisted of a total population of 40 respondents. Data analysis utilized univariate and bivariate analysis with Pearson chi-square statistical testing. The results of the study revealed a significant relationship between manual handling work and complaints of MSDs (p=0.001). With these findings, it is hoped that mine owners, community health centers, and miners can collaborate to provide appropriate education and training on manual handling. Additionally, it is expected that mine owners will implement balanced work and rest schedules to help prevent accidents.